1991
DOI: 10.1016/0010-938x(91)90062-t
|View full text |Cite
|
Sign up to set email alerts
|

Iron dissolution and passivation in K2CO3-KHCO3 solutions. rotating ring disc electrode and XPS studies

Abstract: Rotating ring-disc electrode studies on the anodic dissolution and passivation of iron in potassium carbonate/bicarbonate buffers at 25°C show that in the active anodic dissolution potential range Fe(II) soluble species are generated. This reaction is favoured by the presence of bicarbonate ions in solution and it is explained through the formation of an unstable soluble complex containing Fe(lI) and HCO3 ions. This suggests that the anodic layer at a certain stage of its formation contains some amount of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
21

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 21 publications
4
52
0
21
Order By: Relevance
“…-concentration results in iron dissolution (Castro, Vilche, & Arvia, 1991;Davies & Burstein, 1980;Linter & Burstein, 1999). In addition, Moreno, Morris, Alvarez, and Duffó (2004) demonstrated that high bicarbonate and carbonate increased localised corrosion of carbon steel.…”
Section: Bicarbonate-carbonate Concentrationmentioning
confidence: 99%
See 4 more Smart Citations
“…-concentration results in iron dissolution (Castro, Vilche, & Arvia, 1991;Davies & Burstein, 1980;Linter & Burstein, 1999). In addition, Moreno, Morris, Alvarez, and Duffó (2004) demonstrated that high bicarbonate and carbonate increased localised corrosion of carbon steel.…”
Section: Bicarbonate-carbonate Concentrationmentioning
confidence: 99%
“…To date, its effect has been underestimated because most failures in oil and gas infrastructure are attributed to CO 2 corrosion processes. However, studies show that increasing bicarbonate ion concentration accelerates iron dissolution (Castro, et al, 1991;Davies & Burstein, 1980;Linter & Burstein, 1999) and can influence both the anodic and cathodic reactions (Honarvar Nazari, et al, 2010). The bicarbonate ion (Moreno, et al, 2004) contributes to pitting corrosion (Mao, Liu, & Revie, 1994) and stress corrosion cracking (Might & Duquette, 1996;Pilkey, et al, 1995) in carbon steel pipelines.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations